2019
DOI: 10.1038/s41598-019-53936-2
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-dependent photoelectric properties of MoS2/Si heterostructure solar cells

Abstract: In order to obtain the optimal photoelectric properties of vertical stacked MoS2/Si heterostructure solar cells, we propose a theoretical model to address the relationship among film thickness, atomic bond identities and related physical quantities in terms of bond relaxation mechanism and detailed balance principle. We find that the vertical stacked MoS2/Si can form type II band alignment, and its photoelectric conversion efficiency (PCE) enhances with increasing MoS2 thickness. Moreover, the optimal PCE in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Two-dimensional (2D) layered materials, such as those in the family of transition-metal dichalcogenides (TMDCs) are of considerable interest in nano-optoelectronic applications because of their remarkable optical, electronic, and mechanical properties. As an atomically thin 2D material, molybdenum disulfide (MoS 2 ) has recently been regarded as a promising candidate for the future devices including field effect transistors, photodetectors, solar cells, and energy-harvesting devices requiring high-performance capabilities as a result of its sizable band gap and dielectric constant (ε). In this case, ε is an especially fundamental and important quantity when determining the charge screening, conductance, refractive index, and polarizability outcomes. Therefore, it is crucial to quantitatively measure and calculate the thickness-dependent ε values of MoS 2 film.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) layered materials, such as those in the family of transition-metal dichalcogenides (TMDCs) are of considerable interest in nano-optoelectronic applications because of their remarkable optical, electronic, and mechanical properties. As an atomically thin 2D material, molybdenum disulfide (MoS 2 ) has recently been regarded as a promising candidate for the future devices including field effect transistors, photodetectors, solar cells, and energy-harvesting devices requiring high-performance capabilities as a result of its sizable band gap and dielectric constant (ε). In this case, ε is an especially fundamental and important quantity when determining the charge screening, conductance, refractive index, and polarizability outcomes. Therefore, it is crucial to quantitatively measure and calculate the thickness-dependent ε values of MoS 2 film.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MoS 2 shows considerable theoretical carrier mobility of ~200 cm 2 V −1 s −1 for monolayers and ~500 cm 2 V −1 s −1 for multi-layer [ 24 ]. Similarly, MoS 2 is suggested as an active layer in solar cells due to its high absorption coefficient in the wide visible light range and the enhanced induced drift electrical field [ 25 ]. In a comprehensive review, Das et al [ 24 ] showed that MoS 2 was widely reported as an active layer in heterojunction p-silicon and n-silicon configurations.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The monolayer MoS 2 contains large specific surface areas, strong visible light-absorbing ability, and extreme flexibility against the bulk MoS 2 . [6,11] Such intriguing properties make MoS 2 a perfect alternative material for numerous applications such as photocatalysts, [12,13] photodetectors, [14,15] field-effect transistors, [16] solar cells, [17] and biomedical purposes [18,19] as well as optical fiber sensors (OFS). [10,20] The latter is a well-known sensor due to high sensitivity, noise and electromagnetic interference immunity, compact size, low cost, and multiplex capability.…”
mentioning
confidence: 99%